Arthroscopic-Assisted Anterior Glenoid Reconstruction Using Nonrigid Fixation With Distal Tibia Osteochondral Allograft - Benjamin W. Hoyt MD; Cory A. Riccio MD; John M. Tokish MD; Lance E. LeClere MD; Kelly G. Kilcoyne MD; Jonathan F. Dickens MD (SAGE Publishing, 2023)
Introduction: Traumatic anterior glenohumeral instability events result in a capsulolabral (Bankart lesion) and/or osseous injury with subsequent attritional bone loss, particularly with recurrence. Up to 88% of patients with recurrent instability experience glenoid bone loss, which predisposes to future dislocations and subluxations, even with arthroscopic capsulolabral repair. The surgical management of glenoid bone loss includes a number of different techniques such as the Latarjet or coracoid transfer as well as other osseous and osteoarticular autografts and allografts. However, operative management of shoulder instability has increasingly shifted toward arthroscopic approaches with preservation of anatomy when possible. Indications: Arthroscopic-assisted allograft distal tibia bone block augmentation to the anterior glenoid is indicated for revision anterior glenohumeral instability procedures with anterior bone loss and in primary cases of anterior instability with critical bone loss. Technique: Our technique for nonrigid arthroscopic anterior glenoid reconstruction with allograft distal tibia and anterior labral repair is performed preferentially in the lateral position without necessitating patient repositioning. The preplanned tibial bone block is prepared on a back table prior to the arthroscopic procedure. After creation of portals and elevation of labral tissue, a guide and drill are used to introduce a retrograde reamer which is deployed to create a perpendicular edge for apposition of the allograft tibia. The bone block is then introduced through a rotator interval portal by pulling sutures retrograde through glenoid bone tunnels and is secured to the prepared surface medial to the liberated labrum. The articular surface of the graft and glenoid are aligned and suture-based fixation is used to compress the bone block against the native glenoid. The anterior labral tissue is then mobilized over the graft and repaired to the native glenoid when possible. Description/Conclusion: The benefits of allograft tibia augmentation for anterior instability with glenoid bone loss include an anatomic joint surface restoration including articular cartilage, lack of donor site morbidity, and a minimally invasive arthroscopic approach. When performed arthroscopically and with nonrigid fixation, this technique permits concurrent anterior labral repair and anatomic reconstruction, safe graft passage without necessity of a far medial portal, and expeditious return to function.